Stres Akademik Dengan Prestasi Belajar Masa Pandemi Covid-19 - Eunike Doxa Simanjuntak; Ratriana Y.E. Kusumiati (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2023)
This research is related to academic stress and learning achievement of class VIII D, E and F students at SMP Negeri 3 Magelang during the Covid-19 Pandemic. Coronavirus Disease or Covid-19 is caused by a coronavirus that attacks the respiratory tract, similar to the common cold. Applying the principles of health and safety for families, students, teachers and the community, learning during the Covid-19 period is a distance learning policy, which is applied in schools and universities around the world. However, these various online school requirements trigger academic stress which has an mpact on student achievement. The researcher uses a quantitative research methodology. The results showed that there was a negative correlation between academic stress in the medium category, while the average learning achievement wasi n the high category.